2010
DOI: 10.1007/s10535-010-0024-0
|View full text |Cite
|
Sign up to set email alerts
|

Allelochemical effects on net nitrate uptake and plasma membrane H<sup>+</sup>-ATPase activity in maize seedlings

Abstract: Seven-day-old maize seedlings grown in a nitrogen-free hydroponic culture were exposed for 48 h to 0, 100 and 300 µM trans-cinnamic, p-coumaric, ferulic, caffeic acids, umbelliferone and 200 µM KNO 3 . Net nitrate uptake was affected by trans-cinnamic, ferulic and p-coumaric acids in a concentration-dependent manner, and trans-cinnamic acid appeared to be the strongest inhibitor. Conversely, at low concentrations, caffeic acid stimulated net nitrate uptake while umbelliferone did not influence it. After 24 h o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 28 publications
4
20
0
Order By: Relevance
“…They effect the growth of plants by inhibiting the ions uptake, mainly due to membrane perturbation [38]. The reduced nitrate uptake in maize seedlings at higher concentration of p-coumaric, ferulic acid and trans-cinnamic acid, however lower concentration of caffeic acid enhanced nitrate uptake [39]. The present study also revealed that at dilutions of 0.75 to 1.75 [38] indicated the greater inhibition of ion uptake by phenolic acids (cinnamic acid, benzoic acid).…”
Section: Discussionsupporting
confidence: 54%
“…They effect the growth of plants by inhibiting the ions uptake, mainly due to membrane perturbation [38]. The reduced nitrate uptake in maize seedlings at higher concentration of p-coumaric, ferulic acid and trans-cinnamic acid, however lower concentration of caffeic acid enhanced nitrate uptake [39]. The present study also revealed that at dilutions of 0.75 to 1.75 [38] indicated the greater inhibition of ion uptake by phenolic acids (cinnamic acid, benzoic acid).…”
Section: Discussionsupporting
confidence: 54%
“…Thus, Cucumis sativus (cucumber) and many other crops cannot be grown continuously in the same agricultural sites. Moreover, FA reduces the activities of plasma membrane H + -ATPases (Abenavoli et al 2010) and some hydrolytic enzymes (Devi and Prasad 1992), and alters the nutrient balance in plants (Kobza and Einhellig 1987). Accordingly, methods to enhance FA degradation in soil may enhance agricultural productivity under continuous cropping (Seal et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…; Abenavoli et al . ). Coumarin‐treated plants exhibited a shift in the full induction , which is usually under feedback regulation of N concentration within the roots.…”
Section: Discussionmentioning
confidence: 99%
“…Recent results suggested that some cinnamic acid derivatives, such as trans ‐cinnamic, ferulic and p ‐coumaric acids, affected PM H + ‐ATPase activity independently of NO 3 − uptake (Abenavoli et al . ). However, the coumarin mechanism influencing the NO 3 − uptake system is not yet fully clarified, due to scarce knowledge of functional relationships among anion uptake and PM H + ‐ATPase activity at protein and transcript levels.…”
Section: Introductionmentioning
confidence: 97%